Internationalization of the Renminbi : history, theories and policies - Zhang, Jie 1965- (Enrich series on China's economic issues, 2011)
This series explores the relationship between Chinese banking system reform, regionalization and internationalization of the Renminbi, as well as the possible cooperation between the Renminbi, the Yen, and other Asian currencies. Additionally, the series provides the first comprehensive study of Renminbi internationalization by experts in China and analyzes the currency reform that China will undertake in the current global economy.